Family of Origin Predictors of Marital Outcomes Among Coptic Orthodox Christian Egyptian-American Couples. Issue 1 (2nd January 2019) - Salama, Christina; Jackson, Jeffrey B.; Negash, Sesen; Daneshpour, Manijeh
Abstract: Despite the importance of family within the Coptic community, the extant literature on Coptic family relationships is remarkably limited. The purpose of this study was to explore parental marital quality and family of origin (FOO) quality as predictors of marital satisfaction and marital stability among Coptic Orthodox Christian Egyptian-American couples. Self-report survey data from 255 married Coptic couples living in the United States were analyzed using an actor-partner interdependence model. Results indicated husband FOO quality predicted both marital satisfaction (β =.51, SE = .18, p = .005) and marital stability (β = .51, SE = .22, p = .022) among Coptic husbands but not among Coptic wives. Results further indicated wife parental marital quality, wife FOO quality, and husband parental marital quality were not predictive of marital satisfaction or marital stability among Coptic husbands or wives. Clinical implications, limitations, and recommendations for future research are discussed.